Exploración taxonómica y funcional de la diversidad microbiana en suelos de bosques amazónicos del Perú - Mormontoy Quicaña, Carlo Gustavo (2024)
Amazon forests play a pivotal role in maintaining global ecological balance and are recognized as essential in mitigating climate change impacts. Notably, their soils constitute the largest carbon reservoirs globally and provide a spectrum of crucial ecosystem services. Soil microorganisms serve as primary metabolic drivers, enabling the persistence of carbon within the soil matrix as organic matter. This process is critically modulated by the balance of macronutrients, particularly nitrogen and phosphorus. The efficiency of these metabolic processes, especially those linked to biogeochemical cycling, is largely contingent upon the availability of micronutrients, including essential vitamins. Moreover, external factors such as land-use change and pollution (e.g., artisanal gold mining) may alter microbial community functionality by applying selective pressures on specific microbial populations. Various methodological strategies have been developed to advance our understanding of microbial dynamics, with metagenomics emerging as a leading approach. This technique enables the sequencing of all DNA within a sample, facilitating taxonomic and functional characterization of the integrated microbial community. The present study aimed to assess the microbial diversity of the topsoil within two forest ecosystems in the Peruvian Amazon: the Tambopata National Reserve and the Los Amigos River Conservation Concession (CICRA). These sites represent a mature (primary) forest and an old-growth secondary forest, respectively. Within Tambopata, the plots affected by the natural formation of a canopy gap were compared to the undisturbed plots. The study sought to elucidate variations in the structure of the microbial community as a function of environmental conditions and the unique physiological potential of each soil community. According to the results, these forests are characterized by loam-acid soil and high carbon and nitrogen availability. On the other hand, the subsample sequencing approach followed by merged analyses employed seems optimal for comparative analysis, achieving a per-sample sequencing depth of ∼ 6 Gb, adequate to characterize microbial population assembly with high coverage, though not sufficient for isolation of high-quality metagenome-assembled genomes. The findings suggest that natural disturbances, such as gap formation, do not significantly affect the microbial community structure. However, marked differences were observed between the microbial communities in Tambopata and CICRA soils. Gene-centric analyses, such as those targeting mercury reductase (merA), implicate Mycobacteria in potential responses to mercury contamination within the CICRA forest. Furthermore, the dominant population of Bradyrhizobium across all soil samples likely represents freeliving organisms that, unlike their symbiotic counterparts, may not contribute to nitrogen fixation. Instead, their ecological role may be associated with the environmental provision of cobalamin. This study establishes a foundational framework for monitoring soil microbial communities in the southwestern Amazon, particularly in the context of climate change and the growing anthropogenic pressures on these vital forest ecosystems.